Molecular Assessments, Statistical Effectiveness Parameters and Genetic Structure of Captive Populations of Tursiops truncatus Using 15 STRs - Rocío Gómez; Rocío M. Neri-Bazán; Araceli Posadas-Mondragon; Pablo A. Vizcaíno-Dorado; Jonathan J. Magaña; José Leopoldo Aguilar-Faisal (Animals, 2022)
Genetic analysis is a conventional way of identifying and monitoring captive and wildlife species. Knowledge of statistical parameters reinforcing their usefulness and effectiveness as powerful tools for preserving diversity is crucial. Although several studies have reported the diversity of cetaceans such as Tursiops truncatus using microsatellites, its informative degree has been poorly reported. Furthermore, the genetic structure of this cetacean has not been fully studied. In the present study, we selected 15 microsatellites with which 210 dolphins were genetically characterized using capillary electrophoresis. The genetic assertiveness of this set of hypervariable markers identified one individual in the range of 6.927e13 to 1.806e16, demonstrating its substantial capability in kinship relationships. The genetic structure of these 210 dolphins was also determined regarding the putative capture origin; a genetic stratification (k = 2) was found. An additional dolphin group of undetermined origin was also characterized to challenge the proficiency of our chosen markers. The set of markers proposed herein could be a helpful tool to guarantee the maintenance of the genetic diversity rates in conservation programs both in Tursiops truncatus and across other odontocetes, Mysticeti and several genera of endangered and vulnerable species.